Efforts to Improve Mathematics Learning Outcomes Multiplication Material Through Smart Board Media Class 3 Primary School - Praditya, Arif; Hasanah, Uswatull; Azzahroh, Fatimah; Ou, Qizhong (Journal of Action Research in Education, 2024)
This study aims to determine whether the use of smart board media in mathematics multiplication material can improve the learning outcomes of grade 3 students at UPTD SIN Gili Timur 3. This research uses class action research (PTK). The respondents of this study were grade 3 students at UPTD SDN Gili Timur 3 totalling 5 people, with 2 boys and 3 girls. The results showed that the multiplication smart board learning media can improve student learning outcomes in mathematics subjects multiplication material. The increase in learning outcomes can be seen from: (1) The average score of students in the pre-cycle test is (10.00) which is still in the very poor category. while no student's score reaches the KKM. (2) The average score of students in the Cycle I test is (50.00) which falls into the category of less, while the value of students who reach the KKM is only 1 student or 20%. (3) The average score of students in the Cycle II test is (90.00) which is in the excellent category, while the scores of all students have reached the KKM. This means that during the process of providing action for two cycles, students have increased by (80.00) points. So it can be concluded that the multiplication smart board media has succeeded in improving the ability and learning outcomes of third grade mathematics students of UPTD SDN Gili Timur 3.